Progression of argumentative reasoning and the relation with visual attention in an interactive learning environment - Fang-Ying Yang, Yuan-Li Liu, Shih-Chieh Chien, Yi-Wen Hung (Educational Technology & Society)
In this study, an interactive science learning app on the topic of plate tectonics was developed for tablets to promote argumentative reasoning. The app guided learners through learning stages that required them to propose arguments, identify relevant evidence, acquire background knowledge, and engage in argumentative reasoning in different scenarios. Visual attention during learning was examined using the Tobii Classes 2.0 eye tracking system and analyzed in relation to reasoning performance. Thirty undergraduates (21 female and 9 male) aged 20 to 23 participated in the study. Argumentative reasoning performance was assessed through responses to prompting questions, while visual attention was measured using fixation-based eye movement measures in areas of interest corresponding to different knowledge representations. Descriptive analyses were conducted to illustrate students’ argumentative reasoning performance and visual attention distributions, while correlation and regression analyses were performed to explore associations between visual attention and reasoning performance. The results indicated that students’ ability to use evidence improved over time, with attention shifting from textual to graphical information following exposure to supporting information provided by the learning app. Higher visual attention to data-related information was linked to better reasoning performance.